2002
DOI: 10.4049/jimmunol.168.9.4268
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Identification of an Alternative GATA-3 Promoter Directing Tissue-Specific Gene Expression in Mouse and Human

Abstract: The GATA family of transcription factors regulates development of multiple tissues. Several GATA factors have two promoters directing distinct tissue-specific expression. Although GATA-3 acts in both neuronal and thymocyte development, no alternative promoter usage has been reported. We examined various cell types and tissues for potential alternative GATA-3 transcripts and identified an alternative transcript directed by a promoter located 10 kb upstream of the recognized promoter. Sequences within this promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 29 publications
3
73
0
Order By: Relevance
“…Two distinct promoters control the expression of GATA3 (47). A newly identified promoter is suggested to be responsible for GATA3-dependent GATA3 transcription (GATA3 autoactivation).…”
Section: Discussionmentioning
confidence: 99%
“…Two distinct promoters control the expression of GATA3 (47). A newly identified promoter is suggested to be responsible for GATA3-dependent GATA3 transcription (GATA3 autoactivation).…”
Section: Discussionmentioning
confidence: 99%
“…Murphy and co-workers (57) reported that the expression of GATA3 is controlled by autoactivation. Two distinct promoters (GATA3a and GATA3b) control the expression of GATA3 (49). A newly identified promoter GATA3a is suggested to be responsible for GATA3-dependent GATA3 transcription (GATA3 autoactivation).…”
Section: Discussionmentioning
confidence: 99%
“…5A). Two distinct promoters, GATA3a and original promoter GATA3b have been reported (49), and so we assessed the levels of mRNA of both sites in memory Th2 cells. GATA3a transcripts were detected only in the memory Th2 cells, although the levels were quite low when compared with GATA3b.…”
Section: Memory Th2 Cells Express High Levels Of Gata3 Mrna But Undetmentioning
confidence: 99%
“…There are 2 promoters in the GATA-3 regulatory region, but expression from the distal alternative promoter was detected only in brain 25 thus for our studies the proximal promoter was chosen. CpGs located in the region from 228 up to -115 bp were heavily methylated in undifferentiated cells (up to 90%) but in expressed CD31 molecule and by the end of differentiation procedure (12 th day) all cells participating in tube formation expressed CD105 antigen ( Fig.…”
Section: Resultsmentioning
confidence: 99%